Hábitos de lectura y su influencia en el desarrollo del vocabulario en niños y niñas de 6to. Año de educación básica del centro de Educación Básica Provincia de Imbabura de la ciudad de Santa Rosa, Periodo 2012-2013. - Sánchez Espinoza, Yolanda Marisol (2012)
This research focused on the reading habits and their influence on vocabulary development in children of 6th year of Basic Education Basic Education Center Imbabura Province city of Santa Rosa, problematic context that arises in the educational process and social interaction, for which the investigation proceeded, taking into account that, to the extent that work to improve the teaching-learning process.